Enzymatic synthesis of banana flavour (isoamyl acetate) by Bacillus licheniformis S-86 esterase - Torres, Sebastián (2009)
New carboxylesterase from organic-solvent-tolerant Bacillus licheniformis S-86 strain was characterized. The enzyme named as type II esterase showed an optimal activity in the temperature range 60–65 °C and pH 8.0. The enzyme was moderatly thermostable (half-life of 1 h at 50 °C), but remarkable stable at extremely alkaline pH, retaining 100% of its activity at pH 10.0–11.0. Furthermore, the esterase showed high stability in detergents (86% residual activity in 10% SDS), and also 0.1% ionic and non-ionic detergents are inducers of enzyme activity. PMSF, a serine protease inhibitor, did not show any effect on the activity. The immobilized type II esterase was able to synthesize isoamyl acetate from isoamyl alcohol and p-nitrophenyl acetate (acyl donor) in n-hexane. The resulting ester yield (42.8%), obtained at a low temperature (28 °C) and with a very low amount of enzyme (4.6 × 10−5 mg ml−1), indicates a high potential for type II esterase in isoamyl acetate synthesis for production purposes.